Gamma Ray Spectrometric Analysis of Sand Samples from Selected Beaches along Kenyan Coastline - Willis Otieno Gor Odongo; Nadir Hashim; Margaret Wairimu Chege (The Scientific World Journal)
In this study, the activity concentration levels of 238U, 232Th, and 40K in sand samples collected from Shanzu, Nyali, Kenyatta, Tiwi, Shelly, and Diani beaches selected along the Kenyan coastline were determined using a gamma ray spectrometer with a NaI(Tl) detector. The average activity concentrations of 238U, 232Th, and 40K in sand samples were analyzed as 87 ± 4, 98 ± 4, and 1254 ± 62 Bq/kg, respectively. Also, radium equivalent (Raeq) activity and internal (Hin) and external (Hex) hazard index were calculated to assess the radiological hazards associated with the use of sand samples as building materials. The average values of Raeq, Hin, and Hex were found as 327 ± 16 Bq/kg, 0.98, and 0.72, respectively. The average values of outdoor and indoor annual effective dose rates were estimated as of 0.23 and 0.63 mSv/y, respectively, which are below maximum recommended limit of 1 mSv/y. Generally, these results indicate no significant radiological health hazards for the studied beaches.